Предмет:
МатематикаАвтор:
анонимf(х)\' = (-5х^2 – 13х + 6)’ = (-5х^2)’ – (13х)’ + (6)’ = -5 * 2 * х^(2 – 1) – 13 * х^(1 – 1) – 0 = -10х – 13.
f(х)\' = (х^5 + 20х^2)’ = (х^5)’ + (20х^2)’ = 5 * х^(5 – 1) + 20* х^(2 – 1) = 5 * х^4 + 20 * х^1 = 5х^4 + 20х.
f(х)\' = (-6х^2 – 13х + 9)’ = (-6х^2)’ – (13х)’ + (9)’ = -6 * 2 * х^(2 – 1) – 13 * х^(1 – 1) – 0 = -12х – 13.
f(х)\' = (х^2 – 5х + 9)’ = (х^2)’ – (5х)’ + (9)’ = 2 * х^(2 – 1) – 5 * х^(1 – 1) – 0 = 2х – 5.
f(х)\' = (4х^2 - 9х + 1)’ = (4х^2)’ – (9х)’ + (1)’ = 4 * 2 * х^(2 – 1) – 9 * х^(1 - 1) – 0 = 8х – 9.
f(х)\' = (х^2 - 3х)’ = (х^2)’ - (3х)’ = 2 * х^(2 – 1) - 3* х^(1 – 1) = 2 * х^1 – 3 * х^0 = 2 * х – 3 * 1 = 2х - 3.
Автор:
orionmorrowДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть